Development of ECR ion source with high-temperature superconducting REBCO coils. Issue 1 (1st April 2022) - Chong, T H; Fukuda, M; Yorita, T; Kanda, H; Yasuda, Y; Koay, H W; Morita, Y; Takeda, K; Hara, T; Hisamatsu, M; Zhao, H; Ishiyama, A; et al.
Abstract: A new High-Temperature Superconducting ECR (HTS-ECR) ion source is under development in Research Center for Nuclear Physics (RCNP), Osaka University. This ion source will be used for production of high intensity proton, deuteron and He ion beams. The HTS-ECR magnets are composed of three solenoid coils and a set of sextupole coils made of REBCO tapes, a high-temperature superconductor. The HTS-ECR ion source is designed to operate at frequency of 2.45 GHz and 10 GHz. Performance test of the HTS coils had been carried out at 31 K and 77 K. This HTS coil technology will be applied to development of a meter-size HTS coil system of a high intensity compact AVF cyclotron. This paper introduces the basic design of the HTS-ECR ion source. The performance test results showed that REBCO solenoids remain superconducting state with a current up to 400 A. Simulation results of the magnetic field and electromagnetic field distributions in a plasma chamber fulfilled the requirements of electron cyclotron resonance conditions at 2.45 GHz and 10 GHz. Simulation result of mirror ratios and electromagnetic field amplitudes are also presented in this paper.